2010
DOI: 10.3748/wjg.v16.i42.5324
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic mucosal resection of colorectal polyps in typical UK hospitals

Abstract: EMR for colorectal polyps can be performed safely and effectively in typical UK hospitals. Stricter follow-up is required for histologically advanced lesions due to increased recurrence risk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
18
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 18 publications
1
18
1
Order By: Relevance
“…Most series have reported a higher recurrence rate associated with piecemeal resection as compared to en bloc resection (11,31,33) . Although our findings are consistent with most previous studies, Lim et al (30) found no difference between the two techniques.…”
Section: Discussionsupporting
confidence: 93%
“…Most series have reported a higher recurrence rate associated with piecemeal resection as compared to en bloc resection (11,31,33) . Although our findings are consistent with most previous studies, Lim et al (30) found no difference between the two techniques.…”
Section: Discussionsupporting
confidence: 93%
“…[1][2][3][4] The polyps are snared or removed with diathermy, either en bloc or in a piecemeal fashion.…”
mentioning
confidence: 99%
“…Complications of EMR are less frequent than for standard endoscopic polypectomy. [1][2][3][4][5] The most common adverse event is bleeding (which can be immediate or delayed) and significant bleeding occurs in up to 6.1% of patients. 1 Perforation is uncommon, occurring in 4% of patients, and is suspected in patients complaining of severe abdominal pain not relieved by passing flatus.…”
mentioning
confidence: 99%
See 2 more Smart Citations